Zkscan3 gene is a potential negative regulator of plasma cell differentiation. (May 2019) - Li, Zixuan; Wen, Chunmei; Li, Jialu; Meng, Huimin; Ji, Cheng; Han, Zhichao; An, Gangli; Yang, Lin
We previously showed that the ZKSCAN3 gene codes for a zinc-finger transcription factor that regulates the expression of important genes and plays crucial roles in the development, metastasis, and pathogenesis of rectal cancer, prostate cancer, myeloma, and so on, and in the regulation of autophagy. However, its biological functions under normal physiological conditions remain unclear. In addition, our previous studies showed that the ZKSCAN3 gene may negatively regulate B cell functions. Therefore, we constructed a zkscan3 -knockout mouse model and observed that knockout mice contained a greater number of plasma cells than wild-type mice. We also found that the number of plasma cells was significantly increased in either colorectal cancer xenografts or under lipopolysaccharide-induced conditions. RNA-seq and quantitative-polymerase chain reaction assay indicated that the X-inactive-specific transcript is upregulated in B cells of zkscan3 -knockout mice, which may represent a potential mechanism how zkscan3 modulates plasma cell differentiation.